Escritas juvenis na Educação de Jovens e Adultos: o cotidiano como território cultural de aprendizagens - Beserra, Raquel Carine Martins (2020)
The work studies the relationship between youth and Youth and Adult Education (EJA). The general objective was to understand how youth writings have dialogued or not with EJA in the public school context, in the constitution of their spaces, considering the quotidian as a learning territory. Of the specific objectives, there are: i) Analyze the Youth EJA Project and the school EJA modality in their conceptions, attributions and executions, examining the interstices with the youths; ii) To characterize youth and their cultures written in the daily life of EJA, taking into account the school, the territory, the generations, the ethnicities, the sexualities, the genders and the social classes; iii) To verify the youths' view in relation to the current institutional arrangements of the municipal school EJA to understand the dialogues established. The theoretical-methodological approach had a qualitative character, using participatory research based on the dialectical concept of knowledge as inspiration. The research took as central subjects the youths of two classes of EJA in a municipal public school, located in the neighborhood Presidente Kennedy in the city of Fortaleza. Among the procedures used, there are: participant observation recorded in a field diary, informal conversations, semi-structured interviews and conversation circles with young people. In general, the institutional experiences at EJA took place on the other side of youth, which are routinely associated with the phenomenon of “juvenilization”, which in my view, presented itself as juvenile racism, culminating in a process of “re-schooling”. Otherwise, youth writings presented themselves as cultural boundaries along with the modality, walking side by side, demanding dialogue. Writings that were expressed through their desires, questions, dreams, frustrations, joys, pain, bodies, clothes, antidisciplines, speech, movements and tastes. It is concluded that: a) when the public school does not dialogue with the multiple cultures with which it lives, it tends to strengthen the neocoloniality and the subordination imposed in Latin America and Brazil; b) there is a need to refound the pedagogical practices with youth and other subjects of EJA: adults and the elderly; c) if the modality and the public school does not present itself as a project of social, fair and human development, it will affect in a bad way the groups mainly of blacks, women, LGBTQI +, young people and the popular classes. The thesis to be defended points out that in the weaving of their writings, school and non-school, the youths that, for now, were located in the EJA, signaled in their daily learning territories with traces of re-existences.